Mononuclear ruthenium compounds bearing N-donor and N-heterocyclic carbene ligands: structure and oxidative catalysis. Issue 9 (8th February 2017) - Liu, Hai-Jie; Gil-Sepulcre, Marcos; Francàs, Laia; Nolis, Pau; Parella, Teodor; Benet-Buchholz, Jordi; Fontrodona, Xavier; García-Antón, Jordi; Romero, Nuria; Llobet, Antoni; Escriche, Lluís; Bofill, Roger; et al.
Abstract : Oxidative catalytic properties of Ru II –N5 C complexes containing N -carbene phthalazine-imidazole ligands. Abstract : A new CNNC carbene-phthalazine tetradentate ligand has been synthesised, which in the reaction with [Ru(T)Cl3 ] (T = trpy, tpm, bpea; trpy = 2, 2′;6′, 2′′-terpyridine; tpm = tris(pyrazol-1-yl)methane; bpea = N, N -bis(pyridin-2-ylmethyl)ethanamine) in MeOH or iPrOH undergoes a C–N bond scission due to the nucleophilic attack of a solvent molecule, with the subsequent formation of the mononuclear complexes cis -[Ru(PhthaPz-OR)(trpy)X] n +, [Ru(PhthaPz-OMe)(tpm)X] n + and trans, fac -[Ru(PhthaPz-OMe)(bpea)X] n + (X = Cl, n = 1; X = H2 O, n = 2; PhthaPz-OR = 1-(4-alkoxyphthalazin-1-yl)-3-methyl-1 H -imidazol-3-ium), named1a + /2a 2+ (R = Me), 1b + /2b 2+ (R = iPr), 3 + /4 2+ and5 + /6 2+, respectively. Interestingly, regulation of the stability regions of different Ru oxidation states is obtained by different ligand combinations, going from6 2+, where Ru(iii ) is clearly stable and mono-electronic transfers are favoured, to2a 2+ /2b 2+, where Ru(iii ) is almost unstable with regard to its disproportionation. The catalytic performance of the Ru–OH2 complexes in chemical water oxidation at pH 1.0 points to poor stability (ligand oxidation), with subsequent evolution of CO2 together with O2, especially for4 2+ and6 2+ . In electrochemically driven water oxidation, the highest TOF values are obtained for2a 2+ at pH 1.0. In alkene epoxidation, complexes favouring bi-electronic transfer processes show better performances and selectivities than those favouring mono-electronic transfers, while alkenes containing electron-donor groups show better performances than those bearing electron-withdrawing groups. Finally, when cis -β-methylstyrene is employed as the substrate, no cis / trans isomerization takes place, thus indicating the existence of a stereospecific process.